Advocacia de estado: autonomia institucional e a consolidação do estado democrático de direito - Lima, Daniel Alves Dias Caetano de (2019)
Only after the Federal Constitution of 1988 the Public Attorney was expressly envisaged at the constitutional level, thus, it can not be expected that such a recent institution already has all its contours designed. Therefore, it is proposed to face the controversial question of the autonomy of Public Attorney and its members, analyzing the compatibility between the structure and the functions assigned to that institution. To do so, we will make a brief history beginning with its constitutional forecast, describing its constitutional role and its main activities as an essential function of Justice. Next, we will deal the situation that, currently, arises in the sphere of the organs of the Public Attorney, at federal, state and municipal levels, mainly related to their institutional autonomy, trying to demonstrate that the situation that exists today is not adequate for the performance of its important constitutional function, as well as the consequences thereof. Finally, we will analyze the Public Attorney as a State Attorney and not a Government Lawyer, who, for this, needs the recognition of rights and duties so that their attributions are carried out in a way that is in keeping with the objectives of the institutions to which they belong and, especially, of the Democratic State based on the rule of law.